Kedudukan Sanksi Adat Gampong di Aceh dalam Sistem Hukum Pidana Indonesia - Muhammad Makin; Aditya Nanda Arrafif; Maulana Sena Al Jabbar; Muhammad Rizky Ramadhan (Verdict: Journal of Law Science, 2026)
This study aims to analyze the position of gampong customary sanctions in Aceh within the national criminal law system and their influence on the process of criminal liability. The method used is normative legal research with a statutory approach and a conceptual approach. The results of the study indicate that gampong customary sanctions obtain constitutional legitimacy through Article 18B paragraph (2) of the 1945 Constitution, as well as juridical reinforcement through Law Number 11 of 2006 concerning the Government of Aceh and various related qanun. From the perspective of the national legal system, customary sanctions are part of legal pluralism that is complementary and subordinate to national criminal law. In practice, the resolution of cases through gampong customary mechanisms prioritizes the principles of deliberation and restorative justice, which are oriented toward restoring social relations among perpetrators, victims, and the community. This resolution is generally applied to minor criminal offenses of a social-communal nature. Under certain conditions, customary settlement can influence the formal law enforcement process, including serving as a consideration for law enforcement officials to terminate cases based on a restorative justice approach. However, customary sanctions cannot eliminate criminal liability in cases of serious crimes, as they remain subject to the principle of legality, the supremacy of national law, and the protection of human rights. Thus, the existence of gampong customary sanctions reflects the integration between state law and the living law within society, which enriches the national criminal law system. However, its implementation still requires normative limitations in order to avoid disharmony and legal uncertainty.